PELATIHAN PENGGUNAAN FITUR MAIL MERGE DAN TABLE OF CONTENTS PADA APLIKASI MICROSOFT OFFICE WORD UNTUK SISWA/I SMK NEGERI 1 LOLOFITU MOI - Waruwu, Jurisman; Laia, Ofelius; Gea, Nov Elhan; Lase, Devi Chrisman (Universitas Nias Raya, 2024)
The training on the use of Mail Merge and Table of Contents features in Microsoft Office Word application at SMK Negeri 1 Lolofitu Moi aims to improve students' technical skills in managing documents. The training is designed to help students understand and apply these features in academic and professional contexts. Students were given in-depth understanding and hands-on practice on how to combine standard documents with external data using Mail Merge and how to create an automated table of contents using Table of Contents. The results of the training showed a significant improvement in students' skills, as demonstrated by their ability to complete practical assignments and school projects. The training not only added value to the students' technical competence but also prepared them for the challenges in the world of work.